2020
DOI: 10.1021/acs.jchemed.0c00293
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence on the Effect of an Open-Source Textbook in Second-Year Undergraduate Analytical Chemistry Courses

Abstract: The use of open-source materials is growing in popularity throughout higher education. This Communication investigates the impact on student performance in a second-year undergraduate analytical chemistry course when an open-source textbook is assigned. For two separate semesters, approximately 80 students were enrolled in such a course across five sections. Both student populations had no statistically significant difference across a variety of demographic comparisons, and both achieved a nearly identical ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Perhaps for this reason, the literature does not provide strong evidence that use of OER results in improved student learning outcomes that would result in changed enrollment behavior. Student learning outcomes are generally similar when OER and commercial textbooks are used (Beile et al, 2020;Clinton & Khan, 2019;Cummings-Clay, 2020;Engler & Shedlosky-Shoemaker, 2019;Fialkowski et al, 2020;Fowler et al, 2020;Grinias & Smith, 2020;Hilton, 2020;Jones & Nyland, 2020;Kalaf-Hughes, 2021;Stoval et al, 2019;Vander Waal Mills et al, 2019). Some exceptions are Hardin et al (2019), who found that student learning was significantly increased with the use of OER, and Delgado et al (2019), who found that students performed significantly worse when OER were used.…”
Section: Enrollment Behaviormentioning
confidence: 98%
“…Perhaps for this reason, the literature does not provide strong evidence that use of OER results in improved student learning outcomes that would result in changed enrollment behavior. Student learning outcomes are generally similar when OER and commercial textbooks are used (Beile et al, 2020;Clinton & Khan, 2019;Cummings-Clay, 2020;Engler & Shedlosky-Shoemaker, 2019;Fialkowski et al, 2020;Fowler et al, 2020;Grinias & Smith, 2020;Hilton, 2020;Jones & Nyland, 2020;Kalaf-Hughes, 2021;Stoval et al, 2019;Vander Waal Mills et al, 2019). Some exceptions are Hardin et al (2019), who found that student learning was significantly increased with the use of OER, and Delgado et al (2019), who found that students performed significantly worse when OER were used.…”
Section: Enrollment Behaviormentioning
confidence: 98%
“…In this study, we measured the effect of OERs on performance in general chemistry. Unlike previous work in OER use in chemical education, , students self-selected which materials they would use in the course. Thus, it is important to consider what other factors influence success in general chemistry and control for them as much as possible.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pre-lecture learning modalities typically fall into two broad categories: textbook-based and video-based. Pre-lecture learning from textbooks, the more traditional approach, has been used extensively, but several important roadblocks persist. Frequently, students claim that textbooks are time-consuming to read, contain extraneous content, and have confusing terminology. Consequently, textbook reading assignments often have low completion rates (i.e., low reading compliance), with as few as 3% of students in general chemistry completing reading assignments before class. , Students claim that reading prior to lecture is redundant when similar content will be covered in class in a more concise and understandable manner, suggesting that students are unwilling to adopt regular pre-lecture reading habits because they do not appreciate the usefulness of textbooks for pre-lecture learning. , While it is possible to increase reading compliance, this requires additional accountability measures such as reading quizzes on assigned textbook material. Reading quizzes have been reported to increase student motivation and overall reading compliance, , but instructors are often hesitant to use them in light of student disapproval .…”
Section: Introductionmentioning
confidence: 99%